Pelatihan Pelayanan Prima dan Bahasa Inggris untuk Kantor Depan: Upaya Mewujudkan Layanan Unggul di UPT Destinasi Wisata Terpadu Kabupaten Jember - Indrastana, Nodistya; Kenanga Rinda, Renata; Ismailia, Titik; Rahmanita, Meiga; Diva Apriliana, Amanda; Aziz Rahman Zain, Muhammad; Firllyzeni Angela Firdaus, Kirara (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
High-quality service is the key to a business process because it can build two important things: customer trust and loyalty. Prioritizing customer experience is a valuable investment in today's business world. UPT Destinasi Wisata Terpadu Kabupaten Jember is a work unit that is responsible for managing several tourist destinations. Based on the preliminary study conducted by the community service team, there are 2 problems: the culture of excellent service and the English skills of operational staff at UPT Destinasi Wisata Terpadu are not satisfactory yet. Therefore, the team tried to improve the competence of the operational staff at UPT Destinasi Wisata Terpadu through the Service Excellence and English for Front Office Training. The Service Excellence and English for Front Office Training aimed to improve the operational staff’s customer service and English skills, especially the front office staff. This training will equip the participants with the basic principles of service excellence, effective communication techniques, and strategies for professionally handling complaints. Thus, the participants are not only able to provide satisfactory service, but can also communicate confidently in English. Keywords — Service Excellence, English for Front Office, Excellent Service, UPT Destinasi Wisata Terpadu Kabupaten Jember